2013
DOI: 10.1111/trf.12217
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of murine red blood cells expressing the human KEL glycoprotein induces clinically significant alloantibodies

Abstract: Background Red blood cell (RBC) alloantibodies to non-self antigens may develop following transfusion or pregnancy, leading to morbidity and mortality in the form of hemolytic transfusion reactions or hemolytic disease of the newborn. A better understanding of the mechanisms of RBC alloantibody induction, or strategies to mitigate the consequences of such antibodies, may ultimately improve transfusion safety. However, such studies are inherently difficult in humans. Study Design and Methods We recently gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 48 publications
3
72
1
Order By: Relevance
“…These studies describe a murine model in which polyclonal anti-KEL immunoglobulins are generated through transfusion 24 and are used to examine clearance following passive immunization. The RBC biology of incompatible transfusion in this model is multifaceted, with rapid intravascular clearance of a subset of incompatible RBCs, yet persistent circulation and apparent antigen modulation of other circulating transgenic RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies describe a murine model in which polyclonal anti-KEL immunoglobulins are generated through transfusion 24 and are used to examine clearance following passive immunization. The RBC biology of incompatible transfusion in this model is multifaceted, with rapid intravascular clearance of a subset of incompatible RBCs, yet persistent circulation and apparent antigen modulation of other circulating transgenic RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…23 We have recently reported that KEL2 RBCs transfused into wild-type (WT) recipients induce an anti-KEL glycoprotein response. 24 Herein, we report that anti-KEL immunoglobulins induce antigen modulation on incompatible KEL2 RBCs, with C3 playing a role not only in this antigen modulation but also in cellular clearance. FcgRs likewise contribute to RBC clearance in this Kell model but are not required for antigen modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of anti-KEL IgG subtypes was similar but not identical between animals immunized through transfusion compared with pregnancy ( Figure 7A); recent studies in our laboratory have more fully characterized the time course of IgG and IgM antibody responses post-transfusion. 30 In 3 of 3 experiments (n 5 30 recipients total), 100% of recipients made detectable anti-KEL glycoprotein immunoglobulins after an initial transfusion, which increased further in response to subsequent transfusions ( Figure 7B). This boostable response was not simply due to a continued increase in response after the initial transfusion, For personal use only.…”
Section: Mumt Females Bred Multiple Times With Kel Males Have Healthymentioning
confidence: 99%
“…by guest www.bloodjournal.org From as antibody responses peaked between 14 and 21 days after the initial transfusion; furthermore, this boostable response was not dependent on poly (I:C) pretreatment, as animals transfused in the absence of poly (I:C) also had a boostable anti-KEL response. 30 To determine whether transfusion induced anti-KEL alloantibodies were detrimental to KEL-positive fetuses, wild-type C57BL/6 females who had previously been transfused 3 times with KEL RBCs in the presence of poly (I:C) were bred with KEL-positive males, and pregnancy outcomes were compared with pregnancy outcomes in control females never previously transfused or pregnant. Females immunized through transfusion had smaller litters compared with nonimmunized females ( Figure 7C) (5.5 vs 6.3 pups), fewer total pups alive at weaning per litter ( Figure 7D) (2.6 vs 5.9 pups; P , .05), and fewer KEL-positive pups ( Figure 7E) (22.6 vs 53.1%; P , .05).…”
Section: Mumt Females Bred Multiple Times With Kel Males Have Healthymentioning
confidence: 99%
“…This amount of RBCs was selected for these experiments, given the robust anti-KEL response known to occur following transfusion. 22 Survival of the transfused RBCs was determined by comparing the ratio of circulating KEL to control RBCs in recipients at select time points after transfusion.…”
Section: Blood Collection Fluorescent Labeling and Transfusionmentioning
confidence: 99%